The inner world and Joan Riviere : collected papers, 1920-1958 - Riviere, Joan, 1883-1962.; Hughes, Athol (London ; New York : Published by Karnac Books for the Melanie Klein Trust (London) ; New York : Distributed in the U.S. by Brunner/Mazel, 1991)
Although best known as a disseminator of Freudian and Kleinian ideas, Joan Riviere also contributed important and original material to the body of psychoanalytic literature. This volume presents some of this material and highlights the importance of Riviere's contribution. 376 pages.
CHAPTER FOURTEEN: Kleinian thinking in the 1950sCHAPTER FIFTEEN: Early psychological development: London/Vienna; CHAPTER SIXTEEN: The inner world as seen in literature; CHAPTER SEVENTEEN: An inner world; CHAPTER EIGHTEEN: A last word about Freud; References; Index
Includes bibliographical references (pages 355-362) and index.
Print version record.
English.
WorldCat record variable field(s) change: 650
Keywords: Freud, Sigmund, -- 1856-1939.; Klein, Melanie; Freud, Sigmund, -- 1856-1939.; Klein, Melanie; Psychoanalysis; Subconsciousness; Psychoanalysis; Psychoanalytic Theory; Unconscious, Psychology; Psychanalyse; Inconscient; psychoanalysis; PSYCHOLOGY -- Movements -- Psychoanalysis; Psychoanalysis; Psychoanalysis; Electronic books; Collected Work; Electronic books